Kebijakan Kepala Sekolah dalam Meningkatkan Minat Belajar Peserta Didik pada Pembelajaran PAI - Nilam Sari; Murniyetti Murniyetti (An-Nuha, 2022)
The purpose of this study was to examine the principal's policy in increasing student interest in learning PAI at SMA Negeri 13 Padang. This research uses qualitative research with a case study approach (case study). Sources of data were taken through direct interviews with informants consisting of school principals, Islamic Religious Education teachers, and studentsOverall, the results of the study found that, first, in the aspect of the principal's policy in increasing students' interest in learning in PAI learning, there were four steps taken by the principal, namely implementing a learning policy outside the classroom, making religious events, conducting simulations, then giving punishments. educating according to Islamic law for students who commit violations, as well as giving rewards or awards to students who have a disciplined attitude in good study. Second, the supporting factors experienced by school principals and educators in increasing students' interest in learning are the existence of adequate facilities and infrastructure, cooperation of school elements, collaboration of educators and parents. Third, the inhibiting factors for school principals and educators in increasing student interest in learning are the lack of student knowledge in PAI learning, discipline, family factors, and social influences.